Genetic Variations of PTPN2 and PTPN22: Role in the Pathogenesis of Type 1 Diabetes and Crohn's Disease - Sharp, Robert C.; Abdulrahim, Muna; Naser, Ebraheem S.; Naser, Saleh A. (Frontiers in Cellular and Infection Microbiology, 2015)
Genome wide association studies have identified several genes that might be associated with increase susceptibility to Type 1 Diabetes (T1D) and Crohn's disease. Both Crohn's disease and T1D have a profound impact on the lives of patients and it is pivotal to investigate the genetic role in patients acquiring these diseases. Understanding the effect of single nucleotide polymorphisms (SNP's) in key genes in patients suffering from T1D and Crohn's disease is crucial to finding an effective treatment and generating novel therapeutic drugs. This review article is focused on the impact of SNP's in PTPN2 (protein tyrosine phosphatase, non-receptor type 2) and PTPN22 (protein tyrosine phosphatase non-receptor type 22) on the development of Crohn's disease and T1D. The PTPN2 gene mutation in T1D patients play a direct role in the destruction of beta cells while in Crohn's disease patients, it modulates the innate immune responses. The PTPN22 gene mutations also play a role in both diseases by modulating intracellular signaling. Examining the mechanism through which these genes increase the susceptibility to both diseases and gaining a better understanding of their structure and function is of vital importance to understand the etiology and pathogenesis of Type 1 Diabetes and Crohn's disease.